Measuring Students’ Motivation: Validity Evidence for the MUSIC Model of Academic Motivation Inventory - Brett Jones (International Journal for the Scholarship of Teaching and Learning, 2016)
This study provides validity evidence for the MUSIC Model of Academic Motivation Inventory (MUSIC Inventory; Jones, 2012), which measures college students’ beliefs related to the five components of the MUSIC Model of Motivation (MUSIC model; Jones, 2009). The MUSIC model is a conceptual framework for five categories of teaching strategies (i.e., eMpowerment, Usefulness, Success, Interest, and Caring) that were derived from research and theory as ones that are critical to students’ motivation (Jones, 2009). Participants included 338 undergraduate students who provided questionnaire responses in reference to 221 different courses at a large public U.S. university. Our analyses included classical item analysis, confirmatory factor analysis, the calculation of Rasch measurement scales, and Pearson’s correlation coefficients. Results support the validity of scores produced by the MUSIC Inventory for use with college students. This inventory could be useful to instructors and researchers interested in assessing the effects of instruction on students’ motivational beliefs.